Le vestigia dei gesuati L'eredità culturale del Colombini e dei suoi seguaci - GAGLIARDI, Isabella (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The book analyses the history of the Jesuat congregation, highlighting the elements of connection and comparison with the social contexts, then describing the origin and the most ancient events of the female branch of the congregation, and the memory of the meeting between the "founder" of the Jesuats and the "foundress" of the Gesuate. The iconographic memory of the initiator of the congregation, Giovani Colombini, the collection of the lauds of the Jesuat Bianco da Siena, and the fortune of the 15th-century Life of Giovanni Colombini, written by Feo Belcari, are also investigated. Then the research reconstructs the constellation of groups, religious experiments and bearers of ideas and devotions that were linked to the Jesuats and, in particular, to the convents of Milan, Siena, Lucca, Venice and Rome and the sanctuaries managed by the congregation. The congregational sociability is analysed along its lines: the practice of work as pharmacists and the cultivation of spiritual friendships with prominent people such as the Countess of Guastalla, Lodovica Torelli. Finally, the erudite use of Colombini's Epistolario as a language text is studied. The volume closes with a documentary appendix on the Jesuat convent of Chiusi.